Genetic polymorphisms on temporomandibular disorders: Network meta-analysis - Almeida, Daniel Augusto de Faria; Brant, Camila Freire; da Costa Siqueira, Letícia; Soares, Lélio Fernando Ferreira [UNESP]; Oliveira, Jovânia Alves; de Oliveira, Daniela Silva Barroso; Pigossi, Suzane Cristina; Soares, Carlos José (Elsevier, 2025)
Objective: The aim of this systematic review and network meta-analysis (NMA) is to compare and rank the effects of different genetic polymorphisms on the susceptibility of temporomandibular disorders (TMDs) occurrence. Design: The central question formulated was: “Are genetic polymorphisms involved in the etiology of TMDs?” Following PROSPERO registration (CRD42024507886), electronic searches were conducted in five databases for publications up to November 2024. Results: Sixty-three studies were included in the systematic review and 7 composed the NMA. The qualitative analysis summarized the association between 120 genes (and 206 polymorphisms) and TMDs. Thirty-two polymorphisms (in 24 genes) were linked to overall TMDs, while 22 polymorphisms (in 22 genes) with degenerative bone changes in the temporomandibular joint (TMJ). Additionally, 17 polymorphisms were identified in cases of painful chronic TMD, while 12 polymorphisms in intra-articular disorders. These polymorphisms were in genes related to neurotransmission (COMT, ADRB2, DRD2, ANKK1, SLC6A4 and HTR2A), inflammatory mediators (TNFα, IL10 and MMP1), sex hormones (ESR1and ESRRB), oxidative stress (GSTM1) and bone metabolism (VDR). A protective effect for myalgia occurrence with the COMT_rs165774 polymorphism compared to the wild-type genotype was found in the pairwise meta-analysis (AG genotype: OR: 0.33; 95 %CI: 0.14, 0.76; p < 0.01 and GG genotype: OR: 0.32; 95 %CI: 0.14, 0.74; p < 0.01) and this polymorphism showed the highest probability of being associated with the myalgia (97 %) and arthralgia (93 %) conditions. Conclusions: Genetic polymorphisms in genes related to neurotransmission, inflammatory response, and sex hormones seem to be risk factors related to the TMDs pathogenesis.
Keywords: Polymorphism; Single nucleotide polymorphisms; Temporomandibular joint disorders